Long Noncoding RNA EMX2-AS Facilitates Osteoblast Differentiation and Bone Formation by Inhibiting EMX2 Protein Translation and Activating Wnt/β-Catenin Pathway - Linyuan Fan; Li Zhang; Xin Zhang; Wei Wei; Zhaohui Liu (Stem Cells International)
Long noncoding RNAs (lncRNAs), as a potentially new and crucial element of biological regulation, have gained widespread attention in recent years. Our previous work identified lncRNA empty spiracles homeobox 2 antisence (EMX2-AS) was significantly increased during the osteoblast differentiation of mesenchymal stem cells (MSCs). Overexpression of lncRNA EMX2-AS promoted osteogenesis in vitro and enhanced heterotopic bone formation in vivo, whereas lncRNA EMX2-AS knockdown had the opposite effect. EMX2 could negatively regulate the osteoblast differentiation of MSCs. lncRNA EMX2-AS was 80% expressed in the cytoplasm during osteoblast differentiation in MSCs. Mechanistic analysis revealed that lncRNA EMX2-AS acts as a positive regulator of osteogenic differentiation through interaction with EMX2 and suppression of its expression at the translational level and Wnt/β-catenin pathway is involved in lncRNA EMX2-AS/EMX2 regulated osteogenic differentiation. Our findings not only provide new targets for the treatment of diseases related to osteoblast differentiation disruption but also enrich the understanding of the regulation mechanisms of lncRNA during stem cell differentiation.